2015
DOI: 10.1111/ddg.12548
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychosocial impact of scarring and non‐scarring alopecia in women

Abstract: The psychological burden is heavier and quality of life is more severely impaired among women with scarring alopecia compared with non-scarring alopecia, probably depicting the poorer prognosis of the former.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 26 publications
3
51
0
5
Order By: Relevance
“…Three studies used the DLQI to assess HRQoL in 127 patients with CLE (aged 20–76 years), with women making up to 90% ( n = 73) of the population sampled. Overall, the mean ± SD DLQI score from the three studies ranged from 9·0 ± 6·7 to 12·4 ± 6·4, indicating that having CLE interfered a lot with a patient's HRQoL compared with patients with other skin conditions, such as cutaneous rosacea (4·3 ± 4·6), eczema [8·39 (SD not reported)], psoriasis (8·5 ± 6·0), atopic dermatitis (6·7 ± 6·2) and alopecia (9·4 ± 3·5) . One study reported that DLQI was able to capture the worsening impact on the quality of life in patients with alopecia (also a clinically important difference), thus demonstrating discriminant validity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies used the DLQI to assess HRQoL in 127 patients with CLE (aged 20–76 years), with women making up to 90% ( n = 73) of the population sampled. Overall, the mean ± SD DLQI score from the three studies ranged from 9·0 ± 6·7 to 12·4 ± 6·4, indicating that having CLE interfered a lot with a patient's HRQoL compared with patients with other skin conditions, such as cutaneous rosacea (4·3 ± 4·6), eczema [8·39 (SD not reported)], psoriasis (8·5 ± 6·0), atopic dermatitis (6·7 ± 6·2) and alopecia (9·4 ± 3·5) . One study reported that DLQI was able to capture the worsening impact on the quality of life in patients with alopecia (also a clinically important difference), thus demonstrating discriminant validity .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the mean AE SD DLQI score from the three studies ranged from 9Á0 AE 6Á7 to 12Á4 AE 6Á4, indicating that having CLE interfered a lot with a patient's HRQoL compared with patients with other skin conditions, such as cutaneous rosacea (4Á3 AE 4Á6), 51 eczema [8Á39 (SD not reported)], 52 psoriasis (8Á5 AE 6Á0), 53 atopic dermatitis (6Á7 AE 6Á2) 54 and alopecia (9Á4 AE 3Á5). 55 One study reported that DLQI was able to capture the worsening impact on the quality of life in patients with alopecia (also a clinically important difference), thus demonstrating discriminant validity. 29 This same study reported an interobserver reliability coefficient of 0Á96 (P < 0Á001).…”
Section: Dermatology Life Quality Indexmentioning
confidence: 99%
“…In a study including 23 patients with cicatricial alopecia, 73.9% patients were found to have moderate-to-severe psychosocial impact following the completion of an adapted version of the Woman's Androgenic Alopecia Quality of Life Questionaire (Pradhan, D'Souza, Bade, Thappa, & Chandrashekar, 2011). Recent findings reveal that patients with scarring alopecia reported significantly higher scores on the Dermatology Life Quality Index and Hospital Anxiety and Depression scales when compared with those of patients with nonscarring alopecia (Katoulis et al, 2015). Patients are known to isolate themselves from peers and tend to suffer from anxiety, depression, and low self-esteem.…”
Section: Cicatricial Alopeciamentioning
confidence: 99%
“…Patients are known to isolate themselves from peers and tend to suffer from anxiety, depression, and low self-esteem. Recent findings reveal that patients with scarring alopecia reported significantly higher scores on the Dermatology Life Quality Index and Hospital Anxiety and Depression scales when compared with those of patients with nonscarring alopecia (Katoulis et al, 2015). It is likely that the unfavorable prognosis has a significant impact on the psychosocial burden that is faced by those who suffer from this disorder.…”
Section: Anagen Effluviummentioning
confidence: 99%
“…Universidad de Manizales -Facultad de Ciencias de la Salud Introducción La alopecia es la pérdida anormal del cabello resultado de un proceso patológico, que involucra la unidad pilosebácea, estructura única con múltiples funciones fisiológicas que puede ser fácilmente perturbada por factores sistémicos o locales, siendo esta afección una condición dermatológica muy frecuente, que aqueja hasta al 50% de los hombres y mujeres a lo largo de sus vidas. Hay muchos factores que conducen a la alopecia, incluyendo trastornos autoinmunes e inflamatorios, infecciones, las influencias hormonales, neoplasias, factores físicos o químicos, y los trastornos congénitos [1]. Además, según lo descrito por Guerrero y Kahn [2] existen factores raciales, de edad y sexo que influyen en su génesis.…”
unclassified